Validation of the Duke University Religion Index (DUREL) in Portuguese Cancer Patients Undergoing Chemotherapy - Martinson, Moa (Journal of religion and health, 2021)
Religion is one of the strategies used to cope with life stressful events, particularly in cancer patients. This study aimed to translate, adapt and validate the 5-item Duke University Religion Index (DUREL) into European Portuguese. This is a cross-sectional study in a sample of cancer patients receiving chemotherapy. Data were collected in July-October 2018, and the study was approved by the ethics committee of the institution. A sample of 150 participants was included (64.7% female and 35.3% male), aged 35-83 years, and mainly Catholic (86.7%). Participants who were females, older, had lower education and from evangelical religious traditions scored higher on the total score. The Cronbach’s alpha was 0.89. Factor analysis revealed a one-factor solution. Convergent validity was achieved between DUREL and BIAC (r = 0.78; p < 0.01). The DUREL European Portuguese version is a valid and reliable tool for measuring religious commitment in cancer patients undergoing chemotherapy.